Imaginary economies: the case of the 3D printer - Jens Schröter (Review of Evolutionary Political Economy, 2020)
In the call for the special issue for the EAEPE Journal, we can find the word “scenario.” The question is if the authors can imagine scenarios in which “potential strategies for the appropriation of existing capitalist infrastructures […] in order to provoke the emergence of post-capitalist infrastructures” can be described. Obviously, the call verges on the border of science fiction—and this is not a bad thing. Diverse strands of media studies and science and technology studies have shown (e.g., Schröter 2004; Kirby 2010; Jasanoff and Kim 2015; McNeil et al. 2017) that not only the development of science and (media) technology is deeply interwoven in social imaginaries about possible outcomes and their implicated futures, but there is a whole theoretical tradition in which societies as such are fundamentally constituted by imaginary relations (Castoriadis 1975/2005). But in all these discussions, one notion very seldom appears: that of an “imaginary economy,” meaning a collectively held system of more or less vague or detailed ideas, what an economy is, how it works, and how it should be (especially in the future; but see the somewhat different usage recently in Fabbri 2018). The aim of the paper is to outline a notion of “imaginary economy” and its necessary functions in the stabilization of a given economy, but even more so in the transformation to another economy—how should a transformation take place if there's not at least a vague image where to go? Of course, we could also imagine a blind evolutionary process without any imaginary process but that seems not to be the way in which human societies—and economies—work. Obviously a gigantic research field opens up—so in the proposed paper, only one type of “imaginary economy” can be analyzed: It is the field that formed recently around the proposed usages and functions of 3D printing. In publications as diverse as Eversmann (2014) and Rifkin (2014), the 3D printer operates as a technology that seems to open up a post-capitalist future—and thereby it is directly connected to the highly imaginary “replicator” from Star Trek. In these scenarios, a localized omnipotent production—a post-scarcity scenario (see Panayotakis 2011)—overcomes by itself capitalism: But symptomatically enough, questions of work, environment, and planetary computation are (mostly) absent from these scenarios. Who owns the templates for producing goods with 3D printers? What about the energy supply? In a critical and symptomatic reading, this imaginary economy, very present in a plethora of discourses nowadays, is deconstructed and possible implications for a post-capitalist construction are discussed.
Keywords: B59; O33; O36; P48; Y80; Z19; 320; Imaginary; Science fiction; Discourse analysis; 3D printing